Initial Development of a Modified Trail Making Test for Individuals with Impaired Manual Functioning. Issue 2 (3rd March 2016) - Rane, Shruti; Caroselli, Jerome Silvio; Dickinson, Mercedes; Tran, Kim; Kuang, Fanny; Hiscock, Merrill
Abstract : The Trail Making Test (TMT), a widely used neuropsychological test, is highly effective in detecting brain damage. A shortcoming of the test is that it requires drawing lines and thus is impractical for use with persons suffering manual impairment. The 3 studies described herein were designed to describe and evaluate a nonmanual Trail Making Test (NMTMT) that would be suitable for use with manually impaired individuals. The NMTMT utilizes color to permit oral reporting of the stimuli constituting a series of numbers (Part A) or alternating series of numbers and letters (Part B). The studies, which involved a total of 200 university students, indicate that the standard TMT and the NMTMT are moderately related to each other and have similar patterns of association and nonassociation with other neuropsychological measures. Participants with scores falling near the bottom of the NMTMT distribution have a high probability of scoring at least 1 standard deviation below the mean of the TMT distribution for Part B. The clinically important relationship of Part A to Part B seems to be retained in the NMTMT. It is concluded that the NMTMT shows promise as a substitute for the TMT when the TMT cannot be used.